Geometric, kinematic and dynamic parameters of the disc ripper - V. A. Nikolayev (Вестник СибАДИ)
Introduction. The unit of continuous action for the formation of the underlying layer is designed to increase labour productivity in the construction of roads and other objects, for the construction of which it is necessary to remove the upper layer of soil. For loosening of soil in the unit used bit-like working bodies. Often, disc working bodies are used to cut the soil. Therefore, the expediency of using passive discs in road-building technical means, in particular, in the unit of continuous action for the formation of the underlying layer of highways, is of practical interest. Despite the large number of works, a detailed analysis of the operation of passive disks was not made. Therefore, in order to compare the energy costs for cutting the soil with passive discs and chisel-shaped working bodies, it is necessary to make a theoretical analysis of the operation of passive disks. Analysis of the energy costs of the disk ripper cannot be carried out without having the approximate values of its geometric, kinematic and dynamic parameters.The method of research. As part of a continuous unit to form the underlying layer of roads, each disc would be clamped with soil on both sides and carried out clamped cutting. Therefore, a disk ripper is adopted for analysis, aggregated with a separate energy device. On the basis of the constructive layout, rational geometric parameters of the disk ripper are revealed. The method of calculation of its kinematic and dynamic parameters is developed. In particular, the method of determining the weighted average circumferental velocity of the disk, the angular velocity of the disk and the circumferental velocity of the point on the edge of the disk blade is considered. The modes of cutting the soil by various parts of the disk are considered.Results. On the basis of the developed technique, the dependence of the minimum diameter of the disk on the depth of soil development was revealed. The moment of resistance of the soil to the rotation of the disks is calculated. The horizontal and vertical component of soil resistance to the front disc carrying out clamped cutting and subsequent discs carrying out semi-clamped cutting of the soil are determined. The necessary thrust force of the energy device for cutting the soil with a disk ripper and the dependence of the thrust force of the energy device for cutting the soil on the depth of soil development were revealed. The performance of the unit, including the power device and the disk ripper, is calculated.Conclusion. Since as part of the unit of continuous action for the formation of the underlying layer of roads, the disks will carry out clamped cutting of the soil, for preliminary loosening of the soil with disks, it is more expedient to use a separate unit, including an energy device and a disk ripper. On the basis of the theoretical studies carried out, the necessary thrust force of the energy device for cutting the soil and the total traction force necessary to move the disc ripper were revealed. The performance of the unit is calculated. To compare the energy costs for cutting the soil with passive discs and chisel-shaped working bodies, it is necessary to make a theoretical analysis of the energy costs for the operation of passive disks.